Case report: Combined acute revascularization in early bilateral carotid stent occlusion - Černík, David; Bartoš, Robert; Neradová, Jarmila; Frenštátská, Nicol; Cihlář, Filip; Brušáková, Štěpánka; Sameš, Martin (Frontiers in Neurology, 2022)
Introduction The introduction of a carotid stent involves the use of effective antiplatelet therapy to maintain stent patency. We present a case report of combined acute revascularization in a patient with occlusion in recently introduced stents of both carotid arteries. Methods The patient (male, 73 years) was admitted for stroke recurrence upon discontinuation of antiplatelet therapy. According to the CTA, the closure of implanted stents of both carotid arteries was confirmed. Intravenous thrombolysis and mechanical thrombectomy were performed with complete recanalization of the left carotid stent. At 3 days apart, clinical deterioration was found with progressive stent restenosis. Percutaneous transluminal stent angioplasty, mechanical embolectomy and prolonged low-dose intravenous thrombolysis have been used repeatedly. Results With the impossibility of maintaining the patency of carotid stents even on the maximum drug therapy and despite endovascular procedures, bilateral neurosurgical revascularization of the middle cerebral arteries using ECIC bypasses was successfully performed. Prolonged low-dose intravenous thrombolysis (20 mg recombinant plasminogen aktivator (rTPA) /10 hours) has proven to be an acute bridging therapy until surgery. Conclusion Early occlusion of the carotid stent is a significant complication of endovascular treatment of stenotic arteries. ECIC bypass revascularization of the middle cerebral artery can be a highly effective therapeutic procedure.